Innovation In Population Administration Services - Sari, Ade Risna; Muhsin Efendi; Rulam Ahmadi; Shohib Muslim; Syamsu Rijal (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Population management is one of the services that the local government must offer. The Bandung Regency Government established E-Sakedap in response to widespread public complaints regarding population administration services. Sakedap is an online service for maintaining marriage and divorce certificates for non-Muslims, as well as birth, death, and moving in and out certifications for Indonesian nationals. Data from the research findings were collected, analyzed, and compared using the descriptive qualitative research method. The focus of the study is Sakedap's population administration service innovation in Ciparay Village, Bandung. Kurhayadi claims that the attribute theory of innovation—which takes into account comparative benefits, ease of observation, appropriateness, complexity, and the possibility of trying—is the theory used in the analysis. The research's conclusions, in particular the Sakedap in Program at the Ciparay Village Office, have been able to provide advantages in the form of simpler service because visiting the village is sufficient; visiting the Population and Civil Registry Office is not required. The village is quicker and uses less energy because you don't need to visit as frequently, so there is no need to spend money there either. The implementation of Sakedap is in accordance with the applicable laws, and E-Sakedap is in accordance with the community's demands in order to obtain services that will make population administration easier. There are no problems with Sakedap implementation in Ciparay Village, Bandung. People who lack technological skills and those who think complexity only grows are both wrong. The installation of Sakedap has allowed the community to readily track the scope of the service process for creating population administration records.